THE ROLE OF ORGANISATIONAL CULTURE AND MANAGERIAL PRACTICES IN ENHANCING EMPLOYEE PERFORMANCE AT CLOTHING MANUFACTURING MICRO, SMALL, AND MEDIUM ENTERPRISES (UMKM) IN MEDAN DENAI: A QUALITATIVE STUDY - Syafira Maulida Hasni; sri Mulyani; teguh dwi putra (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze the role of organizational culture and company managerial practices in improvingemployee performance in convection MSMEs in Medan Denai. In the context of increasingly fierce businesscompetition, MSMEs are required to not only rely on production capabilities but also strengthen internalorganizational aspects, particularly work culture and effective managerial practices. This study uses aqualitative approach with a case study method. Data collection techniques were carried out through in-depthinterviews, observation, and documentation of business owners and employees of convection MSMEs.The research results show that a strong organizational culture, such as discipline, teamwork, andresponsibility, plays a crucial role in shaping employee work behavior. Furthermore, managerial practicesincluding open communication, motivation, and a flexible supervisory system have been shown to significantlyimprove employee performance. The combination of a positive organizational culture and adaptive managerialpractices is a key factor in improving employee productivity and work quality.This research provides implications that convection MSMEs need to consciously build a conduciveorganizational culture and implement effective managerial practices to achieve optimal employee performance.Keywords: Organizational culture, managerial practices, employee performance, MSMEs, qualitative research